PERKEMBANGAN SEJARAH DESA KUANTAN BABU : MENGUNGKAP ASAL USUL DAN TRADISI LOKAL - Asyrul Fikri; Febriani Febriani; Frans Yoga Sipahutar; Chairina Nadia; Laurentcia Ananta; Aurora Michelle Angel; Andiny Junila Putri; Danita Aurelia Putri Prameswari; Muhammad Putra Fajar (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
This research aims to explore the history of Kuantan Babu Village, the origins of its formation, and the local traditions that developed among the local community. A qualitative approach was used to trace the development of this village from its founding until now. Apart from that, this research also examineshow local traditions play a role in shaping people's identities and how they adapt to changing times. The research results show that Kuantan Babu Village has a rich history and local traditions that remain sustainable even though they are influenced by modernization.